2011
DOI: 10.4137/cmc.s7189
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Brain Natriuretic Peptide (BNP) as an Indicator of Left Ventricular Function, Early Outcome and Mechanical Complications after Acute Myocardial Infarction

Abstract: Aims:This study investigated the prognostic value of B type natriuretic peptide (BNP) in acute myocardial infarction (AMI) patients and its relation with left ventricular function and post-myocardial infarction complications.Methods:In this cross-sectional study, plasma BNP level was measured for 42 consecutive patients (mean ± SD: 61.6 ± 10.85 years old) with acute ST elevation myocardial infarction (MI) and 42 healthy, age and gender matched subjects.Result:BNP level in AMI patients were significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
1
20
0
1
Order By: Relevance
“…Brain natriuretic peptide (BNP) is a 32-amino-acid ringshaped polypeptide that increases the urinary excretion of water and sodium, relaxes blood vessels and inhibits sympathetic activity (3)(4)(5)(6)(7). Since its use as a drug for heart failure in 2001 (8), recombinant human brain natriuretic peptide (rhBNP) has been increasingly used for the treatment of AMI, accompanied by cardiac insufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Brain natriuretic peptide (BNP) is a 32-amino-acid ringshaped polypeptide that increases the urinary excretion of water and sodium, relaxes blood vessels and inhibits sympathetic activity (3)(4)(5)(6)(7). Since its use as a drug for heart failure in 2001 (8), recombinant human brain natriuretic peptide (rhBNP) has been increasingly used for the treatment of AMI, accompanied by cardiac insufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…28,29) It has been introduced exhibiting various bioactivities, including diuresis, natriuretic function, vasodilatation, and resisting renin-angiotensin-aldosterone system caused by vasoconstrictive effect. 30) The determination of BNP and its N-terminal proB-type (NT-proBNP) is considered valuable for the diagnosis and prognosis of heart failure. 31,32) In patients with heart failure, the levels of BNP are increased in accordance with diseases severity, which is also observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The BNP gene encodes the 108 amino acid prohormone proBNP, which is split into BNP hormone and NT-proBNP in the circulation. Many studies indicated that there was a significant reverse relation between BNP and EF and a significant relationship between BNP and cardiac remodeling in the follow-up [ 29 , 30 ]. By the way, NT-proBNP was found to be a better predictive indicator for infarct size and left ventricle function after AMI in the follow-up [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%